A Guide to Crisis Intervention, 6th Edition - Kristi Kanel (Cengage Learning, 2018)
Handle any crisis situation with the help of this practical, nuts-and-bolts guide. A GUIDE TO CRISIS INTERVENTION, 6th Edition covers the fundamentals of situational and developmental crises, how they occur and how you can manage them. Author Kristi Kanel discusses traditional counseling models as they relate to crisis intervention, and shows how they're incorporated into her ABC Model of Crisis Intervention--which you can use in any mental health setting with anyone in crisis. Examples illuminate the psychological and behavioral dynamics associated with crisis situations. Cases and scripts help you learn exactly what to say to clients, whether the crisis is developmental; related to trauma, post-traumatic stress disorder (PTSD), substance abuse or other factors; or arises from personal victimization. You'll also learn how to conduct suicide assessments and mental status exams.